Expanding the Just Transition to Include Teachers: Composting, Zero Waste and Climate Action in Montreal Schools - McLarnon, Mitchell (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2025)
In the context of the current climate emergency, governments are implementing important climate policies promoting zero waste, carbon neutrality, increased greening, and protection of biodiversity. While climate policies are created with the best of intentions, they obscure the lived experiences of front-line workers attempting to implement these policies in a rapidly changing environment. This article proposes a nuanced understanding of a “just transition” as a promising proposal for climate justice and labour politics. Through drawing on institutional ethnographic approaches to conducting interviews, gathering fieldnotes during observations, and conducting textual analysis, this article connects educational workers’ experiential knowledge with climate policies that shape educational possibilities both locally and extra-locally. By interrogating the enactment of recent zero waste policy from the perspectives of teachers, a principal, and a school board employee, the research findings and discussion increase understanding of how climate change mitigation efforts and policies can produce unequal and unintended effects.